2009
DOI: 10.1002/eqe.911
|View full text |Cite
|
Sign up to set email alerts
|

On the evaluation of seismic response of structures by nonlinear static methods

Abstract: SUMMARYIn the most recent seismic codes, the assessment of the seismic response of structures may be carried out by comparing the displacement capacity, provided by nonlinear static analysis, with the displacement demand. In many cases the code approach is based on the N2 method proposed by Fajfar, which evaluates the displacement demand by defining, as an intermediate step, a single degree-of-freedom (SDOF) system equivalent to the examined structure. Other codes suggest simpler approaches, which do not requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 11 publications
0
19
0
3
Order By: Relevance
“…The scale factor SF, equal to 0.58, is calculated by means of Eq. (26). The maximum demand of storey drift angle (Δ max ) of the buildings is plotted as a function of the behaviour factor adopted in design and is shown in Fig.…”
Section: Considerations On the Limit State Of Damage Limitationmentioning
confidence: 99%
See 1 more Smart Citation
“…The scale factor SF, equal to 0.58, is calculated by means of Eq. (26). The maximum demand of storey drift angle (Δ max ) of the buildings is plotted as a function of the behaviour factor adopted in design and is shown in Fig.…”
Section: Considerations On the Limit State Of Damage Limitationmentioning
confidence: 99%
“…However, these studies refer to frames designed according to seismic codes different from EC8 (e.g. Iranian Earthquake Resistance Design Code or FEMA 302/303) and are sometimes carried out by means of pushover analysis [25], which is not always accurate in the prediction of the seismic response [26][27][28]. Moreover, the modelling adopted in these research studies for BRBs casts a shadow on the accuracy of the obtained results.…”
Section: Introductionmentioning
confidence: 96%
“…This assumption is justified because the present research study is intended to investigate solely the improvement caused by the corrective eccentricities to the prediction of the torsional response. Owing to this, the errors committed by the pushover analysis and regarding the translational response of the structures have been eliminated [10]. In particular, when predicting the floor displacements, the displacements provided by the pushover analysis at each storey of the building are scaled so that the displacement at the centre of mass equals the average of the maximum dynamic displacements of the corresponding planar system.…”
Section: Prediction Of Seismic Response By Nonlinear Static Methods Ofmentioning
confidence: 99%
“…Generally, this method provides reasonable results for planar frames [9][10][11]. Instead, in the case of in-plan irregular structures, it is not always effective.…”
Section: Introductionmentioning
confidence: 94%
“…Also, in [26] it is suggested that a similar equivalent nonlinear SDOF system for asymmetric multi-storey buildings (mathematically derived by two static pushover analyses of the spatial building) could be used in combination with inelastic design spectra. An interesting recent contribution has been made by Bosco et al [27], who suggested an 'N1 method', which does not require the use of an equivalent SDOF model, and avoids the problems related to the bi-linear idealization of the pushover curve, which is required by the N2 method.…”
Section: Introductionmentioning
confidence: 99%